Interaction diversity of North American seed‐dispersal mutualisms. Issue 11 (7th September 2016) - Vander Wall, Stephen B.; Moore, Christopher M.
Abstract: Aim: We determine the prevalence of mutualistic seed‐dispersal interactions across the North American landscape and then test the hypothesis that patterns in interaction diversity are correlated with latitude, longitude, precipitation, midpoint elevation and the elevational range of sites. Location: North America north of the Mexican border. Methods: We used regional plant lists to determine the diversity of animal seed‐dispersal interactions across North America (over more than 48° of latitude). For each plant list ( n  = 197 sites, 12, 424 terrestrial plant species and 123, 519 plant records), we assigned plant species to one of four seed‐dispersal modes (i.e. frugivory, scatter hoarding, myrmecochory or non‐mutualist) and to an animal vector (e.g. bird, carnivorous mammal, rodent, ant). Results: We identified 14 types of animal‐mediated seed dispersal. Plants with seed‐dispersal mutualists are most diverse in the south‐eastern portion of the continent. Dispersal by frugivores and scatter hoarders is strongly negatively correlated with latitude but myrmecochory is not. The diversity of interaction types is significantly correlated with precipitation and elevational range and negatively correlated with latitude, longitude and midpoint elevation. Main conclusions: The diversity of seed‐dispersal mutualisms varies dramatically across the continent, suggesting that the co‐evolutionary processes that produce these interactions are stronger in certain regions and vegetation types and weaker in others. Elucidation of these patterns and their causes will help us to better understand the co‐evolutionary processes that shape communities.